The relationship between inflammatory factors and heart failure: evidence based on bidirectional Mendelian randomization analysis - Xuanchun Huang; Lanshuo Hu; Jun Li; Shiyi Tao; Tiantian Xue (Frontiers in Cardiovascular Medicine)
ObjectiveInflammatory factors play a crucial role in the onset and progression of heart failure. To further explore the causal relationship between inflammatory factors and heart failure, we employed bidirectional Mendelian randomization analysis to investigate the causal links between 91 inflammatory cytokines and heart failure.MethodsWe conducted our study using the bidirectional Mendelian randomization approach. Data on 91 inflammatory factors were sourced from large-scale public genome-wide association study databases, while heart failure data were obtained from the FINNGEN database. The relationships between inflammatory factors and heart failure were evaluated using five methods: MR-Egger regression model, Inverse Variance Weighted method, Simple mode model, Weighted mode model, and Weighted median. Results were subjected to FDR multiple testing correction, and significant findings were discussed in detail. To enhance the robustness of our findings, various sensitivity analyses were conducted, including MR Egger intercept, MR-PRESSO and Cochran Q test.ResultsOur forward Mendelian randomization study indicated that, of the 91 inflammatory factors examined, seven showed a causal relationship with heart failure. Four of these factors were significantly causally related to the incidence of heart failure: CXCL9 and IFN-γ as promotive factors, and LIFR and UPA as potential protective factors. Three inflammatory factors had a potential causal relationship with heart failure, with DNER as a potential protective factor, and MMP-1 and CD6 as potential promotive factors. Reverse Mendelian randomization suggested that the onset of heart failure might potentially influence the levels of four inflammatory factors, with ARTN and FGF5 decreasing after the onset of heart failure, and SLAM and MMP-10 increasing. Additionally, reliability tests of this Mendelian randomization, including MR-Egger intercept and MR-PRESSO tests, revealed no evidence of pleiotropy, and Cochran's Q test also confirmed the reliability of our results.ConclusionWe identified CXCL9, IFN-γ, LIFR, and UPA as potential inflammatory factors associated with heart failure through forward Mendelian randomization. These findings suggest potential targets but require further validation.